Missions, states, and European expansion in Africa - Korieh, Chima Jacob; Njoku, Raphael Chijioke; Beck, Roger B. (African studies, 2007)
Introduction / Raphael Chijioke Njoku and Chima J. Korieh -- All things to all people : Christian missionaries in early nineteenth century South Africa / Roger B. Beck -- The CMS Niger Mission, extra-territorial forces of change, and the expansion of British influence in the Niger Delta during the nineteenth century / Waibinte Wariboko -- Catholicism, Protestantism, and imperial claims in Kabaka's Buganda, 1860-1907 -- Raphael Chijioke Njoku -- Threatening gestures, immoral bodies : the intersection of church, state, and Kongo performance in the Belgian Congo / Yolanda Covington-Ward -- To hang a ladder in the air : talking about African education in Edinburgh in 1910 / Ogbu U. Kalu -- Mission, colonialism, and the supplanting of African religious and medical practices / Jude C. Aguwa -- Conflict and compromise : Christian missions and new formations in colonial Nigeria / Chima J. Korieh -- West Indian Church in West Africa : the Pongas Mission among the Susus and its portrayal of blackness, 1851-1935 / Waibinte Wariboko -- Collaborative landscape : missions, states, and their subjects in the making of northeastern Tanzania's terrain, 1870-1914 / Michael McInneshin -- Anglo-American and European missionary encounters in southern Sudan, 1898-present / Gideon Mailer